The contribution by phytoplankton, bacteria and detritus to a rocky shore ecosystem - Cliff, Geremy (Department of Biological Sciences, 2023)
An investigation has been carried out on the particulate organic matter (IU-1) in suspension over the large inter-- and subtidal reef at Dalebrook in False Bay, standing stocks of hytoplankton, bacteria and detritus were monitored for 13 months, at three localities on the reef, on incoming and outgoing tides. A number of seasonal trends recharge, despite day-to-day variation in t."'1ese stocks. In spring and summer chlorophyll levels were la, 1 - 2 µg/1. Due to the extrerrely lcw nitrate concentrations ( < 2 µg at/1) and to a lesser extent, silicates ( < 6 µg at/1) , little autochthonous phytoplankton production was recorded over this period. Concentrations of nitrates, silicates and chlorcphyll a were highest at the offshore edge of the reef in incoming water. After a strong south-easterly win:i, chlorophyll concentrations of 19 µg/1 were rerorded O, 5 km offshore. Chlorophy 11 concentrations were in the region of 5 µg/1 in winter. Detritus accounted for aln'Ost 80% of the Pa1 and never dropped bela, O, 5 :rrg/1. There were no marked spatial and tidal influences on the mass of detritus in suspension. However, considerable import and export of material is believed to be associated with the strong water m,vements over the reef. Most of the detritus was in advanced stages of deconposition, making it extremely difficult to determine its origin. A Coulter Counter provided particle size spectra over the range 5 - 112 µm. It was found that particles with apparent diameters of 10 - 30 iirn contributed the highest volurre. Bacterial densities ranged fran 4 x 105 to 16 x 105 cells/ml; nurrbers were highest in late surmer and autumn. 95% of the cells were not attached to particles but were free in suspension. These results are canpared with those fran other inshore envirorurents.